The Economics of Social Media - Aridor, Guy; Jiménez-Durán, Rafael; Levy, Ro’ee; Song, Lena (Journal of Economic Literature, 2024)
We provide a guide to the burgeoning literature on the economics of social media. We first define social media platforms and highlight their unique features. We then synthesize the main lessons from the empirical economics literature and organize them around the three stages of the life cycle of content: (i) production, (ii) distribution, and (iii) consumption. Under production, we discuss how incentives affect content produced on and off social media and how harmful content is moderated. Under distribution, we discuss the social network structure, algorithms, and targeted advertisements. Under consumption, we discuss how social media affects individuals who consume its content and society at large, and explore consumer substitution patterns across platforms. Throughout the guide, we examine case studies on the deterrence of misinformation, segregation, political advertisements, and the effects of social media on political outcomes. We conclude with a brief discussion of the future of social media. (JEL D12, D72, D83, D91, I31, L82, M37)